Perencanaan Dan Penyelenggaraan Seminar Nasional Startup di Industri Kreatif Zaman Now Berbasisdigitas Business (Aspek Promosi) - Suryadi, Suryadi; Widodo, Teguh; Domos, Erma (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2021)
This Seminar is one of the activities that has a close relationship with startup companies that operate business in the world of creative industries through the digital business that is currently developing. Specific objectives of the research are to determine the promotion strategy carried out in the planning and implementation, to determine the types of promotion, to knowing the planning and realization of the promotion budget, and the job activity in the field of promotion conducted on the implementation and implementation of the event, knowing the constraints of work done at the time of completion of the project, preparing activity reports in the promotion aspect. The methods used in planning and organizing this seminar consist of project preparation, implementation,  completion and reporting plans. The result of the research indicates that the initial plan of determining the activity plan is then continued with the determination of promotional needs, followed by making a list of donors or sponsorships and looking for donors or sponsors who are willing to become the main sponsor. On donor handouts and sponsorships that will be included in the banners, brochures and mentioned at the agenda of the event in accordance with the specified agreement. While the project reporting form consists of implementation reports and financial reports